CLASSROOM DISCOURSE ANALYSIS - García, Laura (Universidad Autónoma de Nuevo León, 2022)
Introduction Extended participation in sociocultural events and activities accounts for most of an individual's major cognitive, linguistic and social learning (Hall 2002, 186). Since schooling represents one of the most formalized and prolonged sociocultural events for a number of individuals, studying what goes on in the classroom becomes relevant not only for the ones involved, both teachers and students, but for anybody interested in socialization processes. Analyzing classroom interaction can shed light on the processes undertaken for the learner's language as well as teachers, social, and cognitive development. Of special interest for education are the discursive practices, teacher-students, students-students that promote a powerful learning environment and can reflect and/or influence other socio cultural events or practices.